Surviving Savannah [large type] - Henry, Patti Callahan (Thorndike Press large print core, 2021)
"Savannah history professor Everly Winthrop is asked to guest-curate a new museum collection focusing on artifacts recovered from the steamship Pulaski. The ship sank after a boiler explosion in 1838, and the wreckage was just discovered, 180 years later. Everly's research leads her to the astounding history of a family of eleven who boarded the Pulaski together, and the extraordinary stories of two women from this family: a known survivor, Augusta Longstreet, and her niece, Lilly Forsyth, who, along with her child, was never found. These aristocratic women were part of Savannah's society, but when the ship exploded, each was faced with difficult and heartbreaking decisions"--Page 4 of cover.